Maintenance Model to Increase the Availability of CNC Machines, through Lean and TPM tools, in SMEs in the Metalworking Sector - Munive Ruiz, David Daniel (2022)
The operations in the cutting area are one of the most important activities in the metal-mechanic industry; therefore, the aim is to have the highest availability of the cutting machines. This shows how important this procedure is; in this sense, an improvement model is proposed through the application of lean manufacturing tools in a cutting machine, such as SMED, for the reduction of Set Up times; the application of the 5s methodology, to eliminate waste and increase productivity; TPM, to reduce the number of machine failures, together with a detailed maintenance plan. The model was tested by means of the arena software where the main objective was achieved, which was to increase the availability of the cutting machine by 6.45%, since it was possible to decrease the set up time from 15.71 minutes to 13.25 minutes, as well as to decrease the number of machine failures. This research allows SMEs in the metal-mechanic sector to increase their production and, therefore, generate a greater economic benefit.